If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -1) * 7 + -1x = -2x + 3 + 9x Reorder the terms: 4(-1 + 3x) * 7 + -1x = -2x + 3 + 9x Reorder the terms for easier multiplication: 4 * 7(-1 + 3x) + -1x = -2x + 3 + 9x Multiply 4 * 7 28(-1 + 3x) + -1x = -2x + 3 + 9x (-1 * 28 + 3x * 28) + -1x = -2x + 3 + 9x (-28 + 84x) + -1x = -2x + 3 + 9x Combine like terms: 84x + -1x = 83x -28 + 83x = -2x + 3 + 9x Reorder the terms: -28 + 83x = 3 + -2x + 9x Combine like terms: -2x + 9x = 7x -28 + 83x = 3 + 7x Solving -28 + 83x = 3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -28 + 83x + -7x = 3 + 7x + -7x Combine like terms: 83x + -7x = 76x -28 + 76x = 3 + 7x + -7x Combine like terms: 7x + -7x = 0 -28 + 76x = 3 + 0 -28 + 76x = 3 Add '28' to each side of the equation. -28 + 28 + 76x = 3 + 28 Combine like terms: -28 + 28 = 0 0 + 76x = 3 + 28 76x = 3 + 28 Combine like terms: 3 + 28 = 31 76x = 31 Divide each side by '76'. x = 0.4078947368 Simplifying x = 0.4078947368
| 2(2x+4)=5x+4 | | (8x-3y)+(-8x+3y)=16-16 | | 3z+30=51 | | (10m-30)=28 | | X-10=3(X-10) | | y=-0.08x+4.48 | | 5(3r-5)=9r+17 | | 3(2x-5)(2x-5)-(3x-7)(5-2x)=0 | | 2(3x+4)=2x+3 | | 2x+4y=156 | | 4x+-56=12 | | 3(2)-5y=10 | | 24=k(5) | | 3(13-4x)=7-16x | | 3(2)-5=10 | | 3(1)-5y=10 | | 3(0)-5y=10 | | 10x-345=12 | | 3(-1)-5y=10 | | 6x+13y=-15 | | 7x-35=6x | | 47x-241=3 | | 3(-2)-5y=10 | | 35x-250=10 | | -3x+-22=8 | | 15q+-4r=62 | | 76x*220=3230 | | 2x/48=3:12 | | 878574868x=8384748372929 | | 6/11y=19 | | 2*(1/10) | | .002=1/x |